Seismic Performance of Traditional Unreinforced Masonry Building in Nepal - Khadka, Shyam Sundar (Kathmandu University Journal of Science, Engineering and Technology, 2013)
The paper focused on the old traditional buildings, which were constructed more than 100 years ago. Some of these buildings were partially destroyed in 1934 AD earthquake and some of them survived without substantial damage. These unreinforced brick masonry buildings are vulnerable to seismic hazard especially when they are un-reinforced and constructed without special consideration of seismic design. These building are extensively being used and occupied by different governmental and public offices. These buildings were built with best available material during the time of construction with best available technology. However, their seismic resistances are intrinsically limited. Since, at that time no codes were available and no advanced materials of construction like concrete and steel were available, it is assumed that those buildings were made based upon the traditional knowledge and technology. A finite element analysis is carried out in order to reflect the characteristics of the unreinforced masonry (URM) building. A commercial software SAP2000 is used for the analysis. It is found that the existing forms of the buildings are highly vulnerable for future earthquake. For reducing the excessive out-of – plane deformation of the URM building, the loosely connected timber floor should be replaced by the rigid floor or increase the rigidity of the existing floor. Inadequate number of the existing cross wall which makes the large size of the rooms, long unsupported walls and loosely connected existing timber floor are the main drawbacks of the existing form of building. Due to the less number of cross wall connected with longitudinal walls and also the longitudinal direction of the building is more than five times larger than the transverse direction, the whole building cannot acts as a single unit and the longitudinal and transverse walls behaves independently and leads to failure during the earthquake.